The expression profile of circRNA and its potential regulatory targets in the placentas of severe pre-eclampsia - Yuhua Ou; Meilan Liu; Liqiong Zhu; Kewen Deng; Manqi Chen; Hui Chen; Jianping Zhang (Elsevier, 2019)
Objective: To determine the expression profiles of circular RNAs (circRNAs) of women with severe pre-eclampsia (sPE group) versus normal pregnancies (normal control group). Materials and methods: RNA-sequencing (RNA-seq) was conducted to characterize differentially expressed circRNAs and mRNAs in the placental tissues of women with sPE versus normal pregnancies. circRNA functions were predicted by Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) database analysis. The backsplicing junctions of circRNAs were validated with the use of divergent primers. Relative expression levels of cirRNAs were verified by quantitative real-time PCR (qPCR). A circRNA-miRNA-mRNA interaction network was constructed to outline the regulatory network of the differentially expressed circRNAs. Results: A total of 49 differentially expressed circRNAs were found in the placental tissues of women with sPE. Several differentially expressed mRNAs were also observed in the sPE patients. KEGG analysis revealed that the most enriched pathway of the circRNAs was the MAPK signaling pathway, while the differentially expressed mRNAs were primary enriched in pathways in cancer. Among these circRNAs, hsa_circ_0001438, hsa_circ_0001326, and hsa_circ_32340 were upregulated in the sPE patients and the circRNA-miRNA-mRNA interaction network generated with these three circRNAs revealed a broad regulatory network that might be involved in the pathogenesis of sPE. Conclusion: circRNAs are differentially expressed in sPE. The upregulation of hsa_circ_0001438, hsa_circ_0001326, and hsa_circ_32340 has a potential role in the regulation of miRNA and mRNA expression. Changes to the expression profiles of the circRNAs might be linked to the pathogenesis of sPE and could function as biomarkers. Keywords: Severe pre-eclampsia, Circular RNA, RNA-sequencing